Innovation and Productivity a Story of Convergence and Divergence Process in EU Countries - Aikaterini Kokkinou (European Regional Science Association (ERSA), 2006)
Technology is apparently one of the main determining sources of productivity and economic growth and there is a huge literature on productivity, growth and innovation. This paper is aiming to review the main topics related to productivity, growth and innovation activities. In particular, the paper is also aiming to apply some econometric models, in order to estimate the effects of innovation activities to productivity growth in EU member states and to conclude to some safe results and policy implications.
Keywords: 330